(untitled) (International Journal of Atharva, 2024)
This study aimed to explore the investment behavior of undergraduate students focusing on their participation in initial public offerings (IPOs). Data was collected through structured questionnaires from a sample of 321 students out of a total population of 1476 covering management, humanities, and education faculties. The data were collected during two-months period from April 1 to June 1, 2024. The study used exploratory research design with a quantitative approach to analyze data. The study explored that management faculty students are more likely to invest in IOPs compared to humanities faculty and education faculty students. It is also revealed that third and fourth year students were more involved in IPOs than first and second year students. Gender differences in investment behavior were also noted. Male students participate more actively in IPOs than female students. Parental education and profession did not significantly influence the investment behavior. The study pointed-out the need for targeted educational programs to improve financial literacy and informed investment decisions among students.